Вплив механохімічної обробки суміші двох оксидів на базі TiO2 на фізико-хімічні та фотокаталітичні властивості одержаних композитів в деградації метронідазолу - Kiziun, Olena V.; Sachuk, Olena V.; Zazhigalov, Valeriy O.; Kotynska, Liudmyla Yo. (Каталіз та нафтохімія, 2023)
The effect of mechanochemical treatment of oxide composites based on TiO2 (TiO2/ZnO, TiO2/ZrO2, TiO2/MgO, TiO2/SnO2, TiO2/Nb2O5 with a molar ratio of 1:1) on their physical and chemical properties was investigated. It is shown that this treatment leads to a change in the crystal structure of the initial oxides without the formation of new phases, a significant grinding of particles, which is sometimes accompanied by amorphization of both or one of the oxides. As a result of mechanochemical treatment, the specific surface of the composites increases, except for the TiO2/Nb2O5 sample for which grinding is accompanied by agglomeration, which leads to a some decrease in the specific surface. It was established that as a result of the treatment, the morphology of the surface of the compositions changes, and in some cases the elements are redistributed in the near-surface layer. A significant decrease in the size of oxide particles leads to the formation of zones of dense contact between oxides in the composite. The photocatalytic properties of the original compositions and samples after their mechanochemical treatment in the reaction of degradation of metronidazole under ultraviolet radiation were established. It is shown that the photoreaction rate constant and the degree of metronidazole degradation do not depend on the band gap width, which is explained by the greater influence of local activation on the photoprocess than the collective properties of the solid body. It was established that a mixture of titanium oxide with another oxide leads to the formation of an effective catalyst for the photodegradation of metronidazole with a transformation degree of 95-98 % (after 5 hours of reaction), which is 4-7 % higher than that of the original titanium oxide.